Deep Learning with Pytorch Quick Start Guide : Learn to Train and Deploy Neural Network Models in Python. - Julian, David (Packt Publishing Ltd, 2018)
PyTorch is extremely powerful and yet easy to learn. It provides advanced features such as supporting multiprocessor, distributed and parallel computation. This book is an excellent entry point for those wanting to explore deep learning with PyTorch to harness its power.